2021
DOI: 10.3390/ma14020264
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antioxidant Activity of Ursolic Acid by Complexation with Copper (II): Experimental and Theoretical Study

Abstract: The copper (II) complex of ursolic acid (Cu(II) UA) was synthesized and discussed in terms of its infrared, UV–visible spectra, quantum-chemical calculations at B3LYP/6-31G(d) level and antioxidant capacity. The copper (II) complex was stable in methanolic solution with the molar ratio metal:ligand 1:1. The data obtained by FT-IR confirmed the metal ion coordination through the carboxylate anion. The antioxidant properties of ursolic acid and its complex with Cu were discussed on the basis of energy of the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The highest antioxidant activity compared to free phenolic compounds was noted in the case of La(III), Mg(II) complexes of apigenin, Cu(II), Fe(II), La(III), Ce(IV) and oxovanadium (IV) complexes of chrysin, calcium complex of gentisic acid and oxovanadium complex of luteolin (Kalinowska et al, 2020). The research by Samsonowicz et al Samsonowicz et al (2021) proved that Cu(II) complex of ursolic acid was characterized by greater antiradical activity against DPPH • than the ursolic acid alone. It was observed that the higher the concentration of the tested compounds, the greater their antioxidant activity was (Samsonowicz et al, 2021).…”
Section: Metal Complexation Of Phenolic Compounds Could Increase Their Antioxidant Activitymentioning
confidence: 96%
See 4 more Smart Citations
“…The highest antioxidant activity compared to free phenolic compounds was noted in the case of La(III), Mg(II) complexes of apigenin, Cu(II), Fe(II), La(III), Ce(IV) and oxovanadium (IV) complexes of chrysin, calcium complex of gentisic acid and oxovanadium complex of luteolin (Kalinowska et al, 2020). The research by Samsonowicz et al Samsonowicz et al (2021) proved that Cu(II) complex of ursolic acid was characterized by greater antiradical activity against DPPH • than the ursolic acid alone. It was observed that the higher the concentration of the tested compounds, the greater their antioxidant activity was (Samsonowicz et al, 2021).…”
Section: Metal Complexation Of Phenolic Compounds Could Increase Their Antioxidant Activitymentioning
confidence: 96%
“…The research by Samsonowicz et al Samsonowicz et al (2021) proved that Cu(II) complex of ursolic acid was characterized by greater antiradical activity against DPPH • than the ursolic acid alone. It was observed that the higher the concentration of the tested compounds, the greater their antioxidant activity was (Samsonowicz et al, 2021). Świsłocka et al Świsłocka et al (2019) claimed that alkali metal (Li, Na, K) rosmarinates exhibit better antioxidant activity than rosmarinic acid.…”
Section: Metal Complexation Of Phenolic Compounds Could Increase Their Antioxidant Activitymentioning
confidence: 99%
See 3 more Smart Citations